Pengaruh Promosi Penjualan dan Harga Terhadap Peningkatan Penjualan Pada PT. Ori Ginalnest Indonesia - Pandiangan, Jenny Ester (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
One of the elements of marketing is price. On this element can provide guidelines for product pricing. PT. Ori Ginalnest Indonesia has a product price difference that is not too high with competitors’ products. The element of price is also of paramount importance because, in the absence of a definite price in advance it is difficult for companies to establish product quality, conduct sales promotions, and distribute them. Companies use promotions to trigger transactions, making consumers want to buy a particular brand as well as encouraging sales forces to aggressively sell it. In addition promotion is capable of stimulating demand for a product. With the promotion it is expected that the consumers will want to try the product and encourage the existing consumers to purchase the product more often so that repeat purchases will occur and the volume of sales of a company’s products will increase. PT. Ori Ginalnest Indonesia is a trading company engaged in the field of swallow nest sales. As a leading company, PT. Ori Ginalnest Indonesia for the first time conducted the inaugural export of swallow nests from Medan directly to China in March 2017. PT office. Ori Ginalnest Indonesia is located in Williem Iskandar Street. 99 Terrain. Products of PT. Ori Ginalnest is mostly sold to consumers who immediately make a drink from the swallow’s nest for resale, due to the quality of prices and promotions that the company conducts attracts the attention of the consumers. Thus, increase in sales is due to sales promotion and pricing.